Anti-TNF-α Treatment Response in Ankylosing Spondylitis Depends on Gut Microbiota (Precision Medicine Communications, 2022)
Multiple auto-immune diseases are caused by dysbiosis of the gastrointestinal (GI) tract. One such condition is ankylosing spondylitis which is treated using tumor necrosis factor-alpha (TNF-α) inhibitors. It is well known that normal flora of the GI tract interacts with endogenous TNF-α.  Quinghong and associates aimed to investigate the gut microbiome in patients with ankylosing spondylitis that have been administered TNF-α blockers and subsequently identify essential bacteria involved. From 24 ankylosing spondylitis patients and 11 healthy volunteers, fecal samples were analyzed for microbiota profiling using bioinformatic tools and 16S ribosomal DNA amplicons before and after treatment with TNF-α inhibitors. The gut flora profiles of the patients and the healthy controls differed significantly, with a drastically lower amount of short-chain fatty acid (SCFA) producing bacteria observed in the former. Post-anti-TNF α treatment, the patients of ankylosing spondylitis exhibited a positive response where rescue of gut microbiota was seen compared to healthy volunteers. SCFA-producing bacteria- Megamonsa and Lachnoclostridium were significantly lower. Moreover, a negative correlation with disease severity was also observed. Haemophilus and Bacilli, however, may promote disease onset and severity. The investigators, therefore, concluded that gut microbiome, especially SCFA-producing bacteria, can be restored using TNF-α inhibitors in patients suffering from ankylosing spondylitis Pharmacogenet Genomics (2022) DOI: 10.1097/FPC.0000000000000468.